2008
DOI: 10.1634/theoncologist.2008-0055
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Inhibitors: Are There Differences Between Steroidal and Nonsteroidal Aromatase Inhibitors and Do They Matter?

Abstract: Disclosure: W.R.M. discloses that this article discusses letrozole (Novartis), anastrozole (AstraZeneca), and exemestane (Pfizer) for validation of mechanism of action. He has also been on the advisory board for Pfizer and received speaker's honoraria. J.B. has received honoraria and research funding from Pfizer (exemestane). A.M.H.B. has received honoraria and research support from AstraZeneca (anastrozole research). R.W.B. discloses that this article discusses exemestane (Pfizer), anastrozole (AstraZeneca), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 59 publications
0
78
0
2
Order By: Relevance
“…However, this modification almost led to the retention of a comparable cytotoxic effect against the MCF-7 and MDA MB-231 cell lines displaying IC 50 s of 0.75 and 1.20 µM, slightly less than the standard ludartin with IC 50 s of 0.5 and 0.67 µM against the same cancer cell lines, respectively. Among all of the compounds, the parent ludartin (3) and its 1,10-epoxy analog (11) were the most active because of the intact α-methylene-γ-lactone moiety and that the reductive amination at this moiety leads to analogs with a reduced cytotoxic effect, but enhances the cell line selectivity, which was evident from our previous studies as well [7,8]. Surprisingly, the dimethyl amino analogs (12 and 18) of 1,10-epoxy ludartin (11) and ludartin (3) were inactive against all of the cancer cell lines.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…However, this modification almost led to the retention of a comparable cytotoxic effect against the MCF-7 and MDA MB-231 cell lines displaying IC 50 s of 0.75 and 1.20 µM, slightly less than the standard ludartin with IC 50 s of 0.5 and 0.67 µM against the same cancer cell lines, respectively. Among all of the compounds, the parent ludartin (3) and its 1,10-epoxy analog (11) were the most active because of the intact α-methylene-γ-lactone moiety and that the reductive amination at this moiety leads to analogs with a reduced cytotoxic effect, but enhances the cell line selectivity, which was evident from our previous studies as well [7,8]. Surprisingly, the dimethyl amino analogs (12 and 18) of 1,10-epoxy ludartin (11) and ludartin (3) were inactive against all of the cancer cell lines.…”
mentioning
confidence: 70%
“…Among all of the synthesized compounds, only one compound, namely, (11R)-13-[1-(3,4-dimethylphenyl) [1-3] triazol-4-ylmethylamine]-11R,13-dihydroludartin, displayed a potent effect with an IC 50 of 8.5 µM and the parent ludartin molecule displayed an IC 50 of 0.5 µM. Based on the close resemblance of ludartin (3) to arglabin (5) (position isomers), we also synthesized the amino analogs of ludartin [8], wherein compound 9 displayed a selective and potent biological effect, and, finally, we also developed a route for the hemisynthesis of arglabin from ludartin [9]. Arglabin, along with its dimethylamine analog (11R)-13-(dimethylamine)-11,13-dihydroarglabin (6), is an approved anticancer agent in several countries for the treatment of lung, liver, breast, and ovarian cancers [10, 11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that changing from one AI-class to another, regardless of the sequence, can result in 0-26% ORR and that 50-62% of these patients achieve stable disease (Thürlimann et al 1997, Zilembo et al 2004, Bertelli et al 2005, Chia et al 2008, Miller et al 2008. The exact mechanism of nontotal cross-resistance however is not yet known.…”
Section: Perspectivesmentioning
confidence: 99%
“…The development progressed from non-selective to selective non-steroid inhibitors of aromatase, such as letrosol and anastrosol, which block estrogen production (29). The importance of aromatase quantity in tumours was evaluated by Miller et al (31). They observed that most tumours obtain estrogen thanks to both local and peripheral aromatase.…”
Section: Antiestrogens and Phytoestrogensmentioning
confidence: 99%